On the taxonomy of the tribe Pisachini (Hemiptera: Fulgoromorpha: Nogodinidae) with the description of new taxa from China and Vietnam - Meng, Rui; Wang, Menglin; Wang, Yinglun (Zootaxa, 2014)
Goniopsarites gen. nov. is described from China in the tribe Pisachini with G. fronticonvexus sp. nov. as the type species. The genus Pisacha is revised, four new species P. yinggensis sp. nov., P. baculiformis sp. nov., P. falcata sp. nov., P. balteiformis sp. nov. are described, and P. encaustica (Jacobi, 1916) comb. nov. & stat. rev. is reestablished which has been treated as P. naga according to specimens from Taiwan. Identification keys to three genera of the tribe Pisachini and to all species of Pisacha are presented.